Asset or liability? An analysis of the effect of changes in party membership on partisan ideological change. (January 2015) - Rohlfing, Ingo
The role of members of political parties is ambiguous because it entails both benefits and costs. In order to shed light on the question of whether members are an asset or a liability for parties, I examine whether parties use their ideology on a left–right dimension as a collective incentive for the appeal to actual and potential party members. A quantitative analysis of the effects of changes in membership on partisan ideological change, covering 61 parties in 11 Western democracies from the 1950s to the early 1990s, shows that there is a weak, but statistically significant, effect. An additional analysis of two mechanisms by which membership has an effect refutes the alternative explanation that positional changes of the median member account for partisan ideological change. In total, the results indicate that members are both an asset and a liability and that parties try to keep the two in balance.